Post-Annealing Effects on Optical Properties of GaAs/AlGaAs Quantum Dots Grown by Droplet Epitaxy - 서유량; 강태인; 김종수; 송진동; 이상준; 김희대 (한국진공학회, 2023)
The effects of annealing temperature on optical properties for low-temperature growth (LTG) GaAs/AlGaAs quantum dots (QD) were investigated in this study. The LTG GaAs QDs were annealed at temperature of 650, 700, and 750 ？C. From the photoluminescence (PL) results, we found that the PL intensity was enhanced as the annealing temperature was increased and the emission wavelength blue-shifted with increasing annealing temperature. We confirmed that the crystal quality of LTG QD could be improved due to the thermal quarrying effect. The GaAs QD size could be smaller due to Ga out-diffusion and Al inter-diffusion during the thermal annealing process. In photoreflectance spectra, the Franz-Keldysh oscillations above the GaAs band gap become stronger with increasing annealing temperature. The interface electric field strength also increases due to the decrease in the defect density. We thus found that the defect density could be decreased by increasing the annealing temperature.